Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1177/0883073809336933
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Epileptic Spasms in Children With Pallister-Killian Syndrome: A Report of Two New Cases and Review of the Electroclinical Aspects

Abstract: Pallister-Killian syndrome is a rare syndrome of multiple congenital anomalies attributable to the presence of a mosaic supernumerary isochromosome (12p). Although the clinical manifestations of Pallister-Killian syndrome are variable, the most common anomalies include craniofacial dysmorphisms, limb deformities, progressive psychomotor development delay, severe hypotonia, and epilepsy. Standard karyotype is nearly always normal, but the isochromosome (12p) is present in a high percentage of skin fibroblasts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Although it has been previously suggested that most of the patients with PKS who are going to develop seizures do so shortly after birth [Schinzel, 1991], our data suggest otherwise as only eleven (35% or about one third) of the patients with seizures had seizures prior to 1 year of age and neonatal seizures were only reported in one child (2%). Likewise, our findings do support the notion suggested in the five previously described patients [Sanchez‐Carpintero et al, 2005; Yamamoto et al, 2007; Cerminara et al, 2010 also see Table I] that late onset spasms (occurring after 1 year of age, and hence after the typical age of onset for “infantile spasms”) may represent a relatively common epileptic pattern for children with PKS. Although 22% of parents reported that their child had ever experienced status epilepticus, based on subsequent careful review of our survey data, we believe this number to be falsely elevated secondary to parental reporting of longer clusters of tonic spasms as continuous seizure activity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although it has been previously suggested that most of the patients with PKS who are going to develop seizures do so shortly after birth [Schinzel, 1991], our data suggest otherwise as only eleven (35% or about one third) of the patients with seizures had seizures prior to 1 year of age and neonatal seizures were only reported in one child (2%). Likewise, our findings do support the notion suggested in the five previously described patients [Sanchez‐Carpintero et al, 2005; Yamamoto et al, 2007; Cerminara et al, 2010 also see Table I] that late onset spasms (occurring after 1 year of age, and hence after the typical age of onset for “infantile spasms”) may represent a relatively common epileptic pattern for children with PKS. Although 22% of parents reported that their child had ever experienced status epilepticus, based on subsequent careful review of our survey data, we believe this number to be falsely elevated secondary to parental reporting of longer clusters of tonic spasms as continuous seizure activity.…”
Section: Discussionsupporting
confidence: 92%
“…To date, only three groups (Table I) have described the detailed semiology and clinical characteristics of epileptic seizures in a total of five children with PKS [Sanchez‐Carpintero et al, 2005; Yamamoto et al, 2007; Cerminara et al, 2010]. Four of these children had onset of clustered epileptic spasms after infancy (“late‐onset spasms”) and one of these children had an EEG consistent with “modified hypsarrhythmia.” Of these four children, one had onset of “massive myoclonic jerks” at age 13 months that appeared photosensitive in nature, and clustered tonic spasms only emerged later at age 4 [Cerminara et al, 2010]. The last of these five children had onset of partial clonic seizures at age 5.5 years followed by the appearance of clustered tonic spasms in flexion 1 year later [Cerminara et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence of recurrent seizures in individuals with PKS appears to range from 40% to 70% [3,4], but few reports provide much detail regarding the specifics of seizure semiology, treatment options, and response to antiepileptic medications, or prognosis; those that do so describe no more than 2 children per series. Four relatively recent reports [1518] describe a total of 6 children in fair detail, providing considerable information concerning age of onset, clinical semiology and response to treatment. Long-term follow-up is not described.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the hypopigmented streaks reflects the mosaic cytogenetics findings. 9,10 Although epilepsy was reported to affect more than 40% of PK patients, 11,12 and Filloux et al 13 considered epilepsy as one of the triad and as a constant finding in PKS in association with dysmorphism and cognitive impairment, none of our cases developed epileptic fits or even febrile convulsions and their EEG findings were normal. The absence of seizures in our patients could be explained by their relatively young ages.…”
Section: Discussionmentioning
confidence: 51%